Subunit organization in cytoplasmic dynein subcomplexes - King, Stephen J. (Cold Spring Harbor Laboratory Press, 2002)
Because cytoplasmic dynein plays numerous critical roles in eukaryotic cells, determining the subunit composition and the organization and functions of the subunits within dynein are important goals. This has been difficult partly because of accessory polypeptide heterogeneity of dynein populations. The motor domain containing heavy chains of cytoplasmic dynein are associated with multiple intermediate, light intermediate, and light chain accessory polypeptides. We examined the organization of these subunits within cytoplasmic dynein by separating the molecule into two distinct subcomplexes. These subcomplexes were competent to reassemble into a molecule with dynein-like properties. One subcomplex was composed of the dynein heavy and light intermediate chains whereas the other subcomplex was composed of the intermediate and light chains. The intermediate and light chain subcomplex could be further separated into two pools, only one of which contained dynein light chains. The two pools had distinct intermediate chain compositions, suggesting that intermediate chain isoforms have different light chain–binding properties. When the two intermediate chain pools were characterized by analytical velocity sedimentation, at least four molecular components were seen: intermediate chain monomers, intermediate chain dimers, intermediate chain monomers with bound light chains, and a mixture of intermediate chain dimers with assorted bound light chains. These data provide new insights into the compositional heterogeneity and assembly of the cytoplasmic dynein complex and suggest that individual dynein molecules have distinct molecular compositions in vivo.